Nicorandil Induced Oral Ulceration - A Case Report and Review of Literature - Kiranmayi K, Manasa N, Praveen Nagula, Praneeth Polamuri, Anuj Kapadiya, Uday Kiran Anne, Vijaya Lakshmi N, Anjani (International Journal of Innovative Research in Medical Science, 2017)
Nicorandil, an antianginal drug is being commonly used worldwide (except in United States) across the spectrum of the coronary artery disease. It has been recognised as a causative factor for oral ulceration. The aim of this case report is to increase awareness among the cardiologists that nicorandil can induce persistent oral ulceration and thereby look for the same during the follow up in the patients who are prescribed nicorandil.